DNA methyl transferases are differentially expressed in the human anterior eye segment. (16th February 2014) - Bonnin, Nicolas; Belville, Corinne; Chiambaretta, Frédéric; Sapin, Vincent; Blanchon, Loïc
Abstract Purpose DNA methylation is an epigenetic mark involved in the control of genes expression. Abnormal epigenetic events have been reported in human pathologies but weakly documented in eye diseases. The purpose of this study was to establish DNMT mRNA and protein expression levels in the anterior eye segment tissues and their related (primary or immortalized) cell cultures as a first step towards future in vivo and in vitro methylomic studies. Methods Total mRNA was extracted from human cornea, conjunctiva, anterior lens capsule, trabeculum and related cell cultures (cornea epithelial, trabecular meshwork, keratocytes for primary cells; and HCE, Chang, B‐3 for immortalized cells). cDNA was quantified by real‐time PCR using specific primers for DNMT1, 2, 3A, 3B and 3L. Immunolocalization assays were carried out on human cornea using specific primary antibodies for DNMT1, 2 and 3A, 3B and 3L. Results All DNMT transcripts were detected in human cornea, conjunctiva, anterior lens capsule, trabeculum and related cells but showed statistically different expression patterns between tissues and cells. DNMT2 protein presented a specific and singular expression pattern in corneal endothelium. Conclusions This study produced the first inventory of the expression patterns of DNMTs in human adult anterior eye segment. Our research highlights that DNA methylation cannot be ruled out as a way to bring new insights into well‐known ocular diseases. In addition, future DNA methylation studies using various cells as experimental models need to be conducted with attention to approach the results analysis from a global tissue perspective.